Assessing the Role of Mid-day Meal (MDM) on the Nutritional Profile of School Going Children: Snapshot of a Suburban School (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Children’s well-being has been a critical public health concern and an essential determinant of a nation’s overall growth. Although Government has initiated mid-day meal programs particularly in rural areas to improve school-age children’s health and nutrition, data on the nutritional status of sub-urban school children still remain limited. Objective: The present study investigated the nutritional profile of the children receiving mid-day meal (MDM) in a sub-urban school. Methodology: A descriptive, cross-sectional study was conducted among 181 school students of a suburban school in Chattogram. Students from Kinder Garten (KG) level to Class 5 (aged 5-16 years) were interviewed. Sociodemographic, anthropometric and data related to mid-day meal (MDM) were recorded and analyzed. Descriptive statistics were performed using Microsoft Excel. Results: The mean age of the participants was 9.43 ± 2.76 years. Most of them were girls (62.43%). The basal metabolic rates of day shift students (girls: 1154.817 kcal/day; boys: 1083.628 kcal/day) were consistently higher than those of morning shift students (girls: 1025.149 kcal/day; boys: 906.737 kcal/day), indicating age-related physiological differences. Height-for-age Z-scores revealed that 20.54% of girls and 8.68% of boys were stunted. BMI-for-age analysis indicated that 38.24% of boys and 32.77% of girls were underweight. Severe undernutrition (